POLEMIK LAHIRNYA KONSEP QIRÄâAH SABâAH DALAM DISIPLIN ILMU QIRÄâAH - Mustopa, Mustopa (Hunafa: Jurnal Studia Islamika, 2014)
QirÄah is a very important science in the study of the Â UlÅ«m al-QurâÄn.The importance of this science lies not only onÂ  the mehod of how to recite the Qurâan but also on the method of how to understabd Â the meaning of the Koran. In this regard, understanding the formation of qirÄâah Â history in its present formÂ  becomes important, especially Â because Â so rich treasures that the qirÄâah possesses that appeared during the codification of official qirÄah. The standardization of this qirÃ¢ah, on the one hand, gives the muslims a lot ease in reading the Koran; on the other hand, it burries the treasures of the qirÄah science very dynamic during qirÄah sabah codification. This paper discusses the crucial issues related to qirÄâah, including the dark side of its birth to the critical and the objective reading towards the science.Kata Kunci: Aá¸¥ruf, QirÄâah Sabâah, QirÄâah âAsyrah, riwayat, kodifikasi (tadwÄ«n)